2021
DOI: 10.1016/j.matt.2021.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges for aqueous metal-proton batteries

Abstract: Benefiting from fast proton diffusion dynamics, aqueous metal-proton batteries (AMPBs) comprising a proton-storage cathode and a metal anode serve as an emerging system with tremendous potential for high-power energy-storage devices. However, there have been few reports on how to systematically design and construct high-performance AMPBs. Herein, we describe the common proton-storage electrode materials and discuss their desirable features, including high stability in proton insertion/extraction, high compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 73 publications
0
40
0
2
Order By: Relevance
“…A rechargeable aqueous battery with various cationic charge carriers is proposed to meet the above requirements, including monovalent ions (H + , Li + , K + , and Na + ) and multivalent ions (Zn 2+ , Ca 2+ , Mg 2+ , and Al 3+ ). [ 1 , 2 , 3 , 4 ] Although metal‐ion rechargeable batteries possess a high capacity and excellent stability, the ion transport significantly impeded the realization of instantaneous output due to the large ionic radius and strong electrostatic interactions. [ 5 , 6 ] Rechargeable aqueous proton batteries based on the proton uptake/removal mechanism are promising to overcome the ion‐diffusion kinetics limit.…”
Section: Introductionmentioning
confidence: 99%
“…A rechargeable aqueous battery with various cationic charge carriers is proposed to meet the above requirements, including monovalent ions (H + , Li + , K + , and Na + ) and multivalent ions (Zn 2+ , Ca 2+ , Mg 2+ , and Al 3+ ). [ 1 , 2 , 3 , 4 ] Although metal‐ion rechargeable batteries possess a high capacity and excellent stability, the ion transport significantly impeded the realization of instantaneous output due to the large ionic radius and strong electrostatic interactions. [ 5 , 6 ] Rechargeable aqueous proton batteries based on the proton uptake/removal mechanism are promising to overcome the ion‐diffusion kinetics limit.…”
Section: Introductionmentioning
confidence: 99%
“…[9,17,18] Moreover, benefited from Grotthuss mechanism, protons in aqueous electrolytes and in electrode materials would exhibit high ionic conductivity, facilitating the reaction kinetics and rate capability. [19][20][21] Up to now, metal oxides, prussian blue analogues (PBA), and organic materials have been explored as cathode materials of proton batteries. Gogotsi et al reported the proton-intercalation chemistry in MnO 2 based on surface reactions.…”
mentioning
confidence: 99%
“…Moreover, the ionic conductivity of aqueous electrolytes is usually orders of magnitude higher than for the organic electrolytes, which enables fast electrochemical reactions during processing. [ 8–11 ] Consequently, the aqueous‐based energy storage technologies are attracting more and more attention worldwide in recent years.…”
Section: Introductionmentioning
confidence: 99%